Ideologi perempuan Timor dalam film Salam: Sahabat Alam - Adam, Lenny Nofriyani; Sudana, Dadang; Shiyabuddin, Shiyabuddin; Muttaqin, Zainul; Sari, Nila Puspita; Amaliana MZ, Zulfiana (Universitas Mulawarman, 2025)
This study aims to explore how the film Salam constructs and presents the ideology of Timorese women through female characters’ utterances and visual sequences laden with symbolic meaning and social discourse. The research employs Norman Fairclough’s Critical Discourse Analysis (CDA), integrating three dimensions: textual analysis, discourse practice, and social practice. The data consist of transcriptions of female characters’ dialogues and selected key visual screenshots, analyzed to reveal their embedded ideological representations. The findings indicate that Salam portrays Timorese women not merely as domestic figures but also as guardians of tradition, ecological agents, and active participants in culturally rooted social resistance. The dialogues emphasize communal values, spiritual ties to ancestral land, and resistance to external forces such as mining exploitation. Visuals—such as scenes of weaving in public spaces and praying before the statue of the Virgin Mary—reinforce a localized ecofeminist ideology that intertwines custom, ecology, and religiosity. A unique finding of this study is the ideological shift of women from domestic spheres to public arenas, using cultural practices as a form of counter-hegemony. This research highlights how local visual media serve as a vital platform for articulating women’s ideologies and the cultural wisdom of indigenous communities.